Estratégias argumentativas sobre a vacinação pediátrica contra Covid-19: o discurso de Jair Bolsonaro e Marcelo Queiroga - Rostan, Fernanda de Souza Couto (2023)
The authorization of pediatric vaccines against Covid-19 in Brazil was permeated by misinformation and controversial positions, especially in the speeches of former President of the Republic Jair Messias Bolsonaro and former Minister of Health, Marcelo Antônio Cartaxo Queiroga. This research focuses on analyzing these manifestations of the two public actors, in their speeches quoted directly and indirectly in the online newspapers GZH and Poder 360, both members of The Trust Project - an international consortium of vehicles that share indicators aimed at the credibility of news content - the first being focused on general news and the second specializing in stories about politics and power. It also analyzes the personal accounts of the social network Twitter of the two public actors. The theoretical basis on disinformation comes from the studies by Wardle and Derakhshan (2017) and Recuero et al (2018, 2020, 2021, 2022). The methodology applied to carry out the analysis is that of the theories of Argumentation, developed by Charaudeau (2006, 2007, 2022), Breton (2003) and Amossy (2018). In this way, we seek to identify the arguments most used by Bolsonaro and Queiroga to talk about the pediatric vaccine, whether or not there are differences between the manifestations dedicated to the press and those directed at followers on social networks, based on the hypothesis of the use of public disinformation in discourse, which is when a public actor, that is, a holder of public office, either by career, appointment or election, discloses disinformation, as being truthful and accurate information. Among the main conclusions of the research is the use, by Jair Bolsonaro, of denialism as an argumentative strategy to give statements to the press, as well as resorting to the use of public disinformation in his speeches. Concomitantly, on Twitter, the subject of pediatric vaccination was silenced by the former president, demonstrating that there was a previously designed strategy to address the subject in different media. The strategic approach to the subject is also perceived in Marcelo Queiroga's speech, which resorts, as a priority, to the argument of authority: in the press to value Bolsonaro; on Twitter, to highlight the work of the Ministry of Health. About the media studied, GZH and Poder 360, there was a continuous repetition of the same speeches of the two public actors, in different contents, which can potentiate the circulation of disinformation, even if it is in news that deconstructs distorted information - after all, each time it is presented by the press, it can reach audiences not previously reached, as well as giving visibility to the disinformation given.